2020
DOI: 10.1177/0846537119899526
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomic Models Using Machine Learning Techniques to Predict EGFR Mutations in Non-Small Cell Lung Cancer

Abstract: Background: The purpose of this study was to build radiogenomics models from texture signatures derived from computed tomography (CT) and 18F-FDG PET-CT (FDG PET-CT) images of non-small cell lung cancer (NSCLC) with and without epidermal growth factor receptor ( EGFR) mutations. Methods: Fifty patients diagnosed with NSCLC between 2011 and 2015 and with known EGFR mutation status were retrospectively identified. Texture features extracted from pretreatment CT and FDG PET-CT images by manual contouring of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…In total, 33 studies investigating radiomics and biological endpoints for lung lesions were identified. The imaging modalities employed were CT ( n = 22) [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], PET/CT ( n = 8) [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ], PET ( n = 2) [ 100 , 101 ] and MRI ( n = 1) [ 102 ]. One study investigated radiomics from metastases, while all other studies associated tissue biomarkers with radiomics of the primary tumor.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 33 studies investigating radiomics and biological endpoints for lung lesions were identified. The imaging modalities employed were CT ( n = 22) [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ], PET/CT ( n = 8) [ 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ], PET ( n = 2) [ 100 , 101 ] and MRI ( n = 1) [ 102 ]. One study investigated radiomics from metastases, while all other studies associated tissue biomarkers with radiomics of the primary tumor.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a ML model using CT radiomics and clinical features achieved a diagnostic accuracy of 88.3% in the external validation dataset for predicting EGFR mutant NSCLC [ 59 ]. Additionally, PET-imaging derived radiomic features have also been used to predict EGFR mutation status with accuracies around 75–78% [ 60 , 61 ]. The development of the T790M mutation in EGFR, which can occur during treatment with first-generation EGFR tyrosine kinase inhibitors (gefitinib and erlotinib) is an important mechanism of resistance.…”
Section: Ai For Biomarker Discovery From Medical Imaging To Biologymentioning
confidence: 99%
“…The application of quantitative imaging to identify epidermal growth factor receptor mutation status was assessed for non-small cell lung cancer. 11 This study found that CT texture analysis could be used to differentiate wild type and mutant epidermal growth factor receptor (EGFR) variants. Both CT texture analysis and FDG-PET texture analysis could be used to differentiate EGFR wild type and mutant, with entropy and kurtosis being the most important texture analysis features.…”
Section: Innovationmentioning
confidence: 99%
“…However, FDG-PET texture analysis showed superior performance for differentiating between types of EGFR mutations. 11 Tumors with EGFR mutations are more likely to respond to tyrosine kinase inhibitor therapy and obtaining this information pre-surgery could accelerate initiation of systemic treatment.…”
Section: Innovationmentioning
confidence: 99%